The Performance of a Disk Plow Combined with a Rotary Blade in Wet Clay Soil - Amran, Faizal Amri (1997)
An investigation was initiated to obtain some understanding on the behavior of wet clay soil and to explore the potential of combined operation of disk plow and rotary blade to reduce travelling of machine in paddy field. Tests were conducted in a soil tank 20 m long, 3 wide, and .75 m deep, the Munchong soil was used and soil condition was controlled. A 25 HP tractor was modified as the prime mover. Frame to put disk plow and rotary blade was designed. An extended octagonal ring dynamometer was used to draft measuring and torque transducer to torque measuring. Based on the existing information about disk plow-soil parameters, the effects of forward speed, disk angle, tilt angle and width of cutting were explored. Results between soil-disk parameter design were compared and the flow of soil slice on disk surface was determined. This would give some indication of the effect of soil-disk parameter and its initial wet soil flow on disk surface. The result of plowing wet soil shows that tilt angle had no statistically significant effect on draft. The forward speed has main effect of design parameter on force requirement. Studies on soil flow on disk surface had shown that upward soil flow was more prominent causing soil clogging as the forward speed increased. Increasing of disk angle and tilt angle increased soil clogging on disk surface. Based on the experiments flow on wet soil furrow slice on disk surface, the location of rotary blade was determined. The effects of forward speed, rotary speed, disk angle, tilt angle and width of cutting were explored. Results between soil-combined disk plow and rotary blade parameter design were compared and the flow of soil slice on disk surface determined. The forward speed and rotary speed have the main effect of design parameter on torque requirement. Increasing of rotary speed will decrease force requirement of disk plow. The use of a rotary blade with reversed rotation is an effective method to reduce force requirement. Distance of soil furrow slice on disk surface increases when the rotary speed increases. The combination of forward speed and rotary speed determined the length of soil slice.